Reinterpretation Of QS. al-A‘Râf [7]:11-25 On Hoax: Hermeneutics Study Of Ma’na-Cum-Maghza - Abdul Muiz Amir (Jurnal Ushuluddin, 2019)
This article examines the interpretation of QS. al-Araf [7]: 11-25 by dialoguing the story of the Success of Adam and social reality. Dialogue that discusses the issue of the history of hoax, the strategy of making hoax, the impact, and handling of hoax issues. This research uses qualitative with hermeneutics ma'na-cum-maghza  theory. This interpretation shows that hoax are phenomena that have existed since the beginning of human kind (Prophet Adam). The unfair contestation and an inability to accept differences caused the policy tendency. This hoax strategy is carried out through logical agreement and approving of oaths that seem right. How to handle habits can only be done through internalizing the nature of sincerity and waiting as a form of grace to accept all forms of diversity, and to cultivate a critical nature of all information received. Besides, the government also needs to take and resolve not only to provide punishment to the victims but also need to get rehabilitation to avoid prolonged depression